2011
DOI: 10.1104/pp.111.174979
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and 1-Methylcyclopropene Differentially Regulate Gene Expression during Onion Sprout Suppression    

Abstract: Onion (Allium cepa) is regarded as a nonclimacteric vegetable. In onions, however, ethylene can suppress sprouting while the ethylene-binding inhibitor 1-methylcyclopropene (1-MCP) can also suppress sprout growth; yet, it is unknown how ethylene and 1-MCP elicit the same response. In this study, onions were treated with 10 mL L 21 ethylene or 1 mL L 21 1-MCP individually or in combination for 24 h at 20°C before or after curing (6 weeks) at 20°C or 28°C and then stored at 1°C. Following curing, a subset of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
7
30
1
Order By: Relevance
“…Ethylene might enhance the level of glucose (Foukaraki et al 2012), and the effect reversed with increasing content of ethylene. Cools et al (2011) observed that the levels of three sugars in onion were decreased to a variable extent on ethylene treatment which was consistent agreed with our results.…”
Section: Sucrose Fructose and Glucose Contentsupporting
confidence: 82%
“…Ethylene might enhance the level of glucose (Foukaraki et al 2012), and the effect reversed with increasing content of ethylene. Cools et al (2011) observed that the levels of three sugars in onion were decreased to a variable extent on ethylene treatment which was consistent agreed with our results.…”
Section: Sucrose Fructose and Glucose Contentsupporting
confidence: 82%
“…There are multiple reports describing the cross-talk of different phytohormones associated with dormancy break and sprout leaf elongation ( Hartmann et al, 2011 ; Cools et al, 2011 ; Chope et al, 2012 ), as well as with mobilisation of non-structural carbohydrate reserves ( Davis et al, 2007 ), particularly fructans ( Valluru, 2015 ; Ohanenye et al, 2019 ). In general, sprout elongation is thought to be initiated by the action of promoting hormones, such as CKs and gibberellins whilst being suppressed by the antagonist action of the inhibitory hormone ABA.…”
Section: Introductionmentioning
confidence: 99%
“…HMGR, catalyzing the conversion of HMG-CoA to mevalonic acid, is considered as a rate-limiting enzyme in cholesterol synthesis, and it also plays a critical role in controlling isoprenoid derivatives related pathways (Chen et al 2012). Cools et al (2011) found that ethylene treatment could increase in the expression of HMGR gene in onion. HMGR gene expression was induced by elicitor in Michelia chapensis (Cao et al 2011).…”
Section: Discussionmentioning
confidence: 98%